Effects of titanium on microstructure and mechanical properties of ZnAl4Y alloy - Wang Jianhua; Wang Xiande; Tu Hao (China Foundry, 2011)
The effect of Ti on the microstructure and mechanical properties of zinc-aluminum ZnAl4Y alloy has been investigated in this work. Small amount of Ti was added into ZnAl4Y alloy in the form of Al-10wt.%Ti alloy. The results show that Ti addition into ZnAl4Y alloy refines the primary η-Zn phase and increases the amount of η-Zn + α-Al eutectic structure. There exists a ternary T phase in Zn-Al-Ti alloy. Fine TiAl3 particles and Ti-Zn compounds can serve as the nucleation sites of the α-Al and η-Zn phase, respectively, resulting in the refining of the microstructure of ZnAl4Y alloy. Ti addition changes the fracture characteristics of ZnAl4Y alloy. With 0.05wt%Ti, the fracture surface of the alloy shows a lot of dimples and tearing ridges connecting the microscopic dimples, which is mainly ductile fracture morphology. Ti addition into ZnAl4Y alloy also increases the mechanical properties of the alloy. When the content of Ti is 0.05wt.%, the ZnAl4Y alloy possesses the best comprehensive mechanical properties.